Manfaat Senam Hamil untuk Mengurangi Nyeri Punggung pada Ibu Hamil Trimester Ketiga - Leni Rozani; Ferasinta, Ferasinta (Bengkulu Institute, 2023)
Pregnancy is a transition between life before and after the birth of a child. This change is considered a period of undergoing a preparation process both physically and psychologically. Complaints caused by an enlarged stomach, anatomical changes and hormonal changes will cause complaints in pregnant women such as low back pain, back pain, swelling and cramps in the legs. Efforts to overcome this include exercise and relaxation exercises that are suitable for pregnant women, namely pregnancy exercises. The aim of this activity is to reduce complaints of back pain in third trimester pregnant women. Activities are carried out for all pregnant women at the Susi Midwife Practice. Activities are carried out by providing pregnancy exercise interventions. The time required is 20 minutes. There is a decrease in back pain in pregnant women.